A look at the intergenerational associations between self-compassion, body esteem, and emotional eating within dyads of mothers and their adult daughters. (June 2020) - Carbonneau, Noémie; Goodman, Lynnel C.; Roberts, Lindsey T.; Bégin, Catherine; Lussier, Yvan; Musher-Eizenman, Dara R.
Highlights: Self-compassionate women have a positive relationship with food and their body. Daughters of self-compassionate mothers report lower emotional eating. Body esteem mediates the association between self-compassion and emotional eating. Mothers appear to transmit their self-views and eating behaviors to their daughters. Abstract: Research has demonstrated that mothers transmit body-related attitudes and eating behaviors to their daughters, but little is known about the role of self-compassion—treating oneself with kindness and being mindful about one's experiences—in this transmission. This research examined the intrapersonal and interpersonal associations between mothers' and daughters' self-compassion, body esteem (i.e., positive self-evaluations about one's appearance), and emotional eating (i.e., the tendency to eat in response to negative affect). Dyads ( N  = 191) of Canadian mothers (mean age: 57.37) and daughters (mean age: 28.76) completed self-report questionnaires. Dyadic, structural equation modeling and bootstrapping analyses were conducted to examine relationships among the study variables. Controlling for mothers' and daughters' body mass index, self-compassionate mothers and daughters reported higher body esteem. Additionally, daughters of self-compassionate mothers were more self-compassionate and had higher body esteem, which in turn predicted lower emotional eating. Adding to the literature on the intergenerational transmission of eating-related attitudes and behaviors, results suggest a relation between mother and daughter self-compassion, body esteem, and eating behaviors. Results also showed that attitudes toward oneself were related to eating behaviors. Mothers' self-compassion might provide a model for daughters, which in turn is associated with daughters' improved body esteem and eating behaviors.